Effect of High Temperature Stress During the Reproductive Stage on Grain Yield and Nutritional Quality of Lentil (Lens culinaris Medikus) - Choukri, Hasnae; El Haddad, Noureddine; Aloui, Khawla; Hejjaoui, Kamal; El-Baouchi, Adil; Smouni, Abdelaziz; Thavarajah, Dil; Maalouf, Fouad; Kumar, Shiv (Frontiers in Nutrition, 2022)
High temperature during the reproductive stage limits the growth and development of lentil (Lens culinaris Medikus). The reproductive and seed filling periods are the most sensitive to heat stress, resulting in limited yield and nutritional quality. Climate change causes frequent incidents of heat stress for global food crop production. This study aimed to assess the impact of high temperature during the reproductive stage of lentil on grain yield, nutritional value, and cooking quality. Thirty-six lentil genotypes were evaluated under controlled conditions for their high-temperature response. Genotypic variation was significant (p < 0.001) for all the traits under study. High temperature-induced conditions reduced protein, iron (Fe) and zinc (Zn) concentrations in lentils. Under heat stress conditions, mineral concentrations among lentil genotypes varied from 6.0 to 8.8 mg/100g for Fe and from 4.9 to 6.6 mg/100g for Zn. Protein ranged from 21.9 to 24.3 g/100g. Cooking time was significantly reduced due to high-temperature treatment; the range was 3 to 11 min, while under no-stress conditions, cooking time variation was from 5 to 14 min. Phytic acid variation was 0.5 to 1.2 g/100g under no-stress condition, while under heat stress condition, phytic acid ranged from 0.4 to 1.4 g/100g. All genotypes had highly significant bioavailable Fe and moderately bioavailable Zn under no-stress conditions. Whereas under heat stress conditions, Fe and Zn bioavailability was reduced due to increased phytic acid levels. Our results will greatly benefit the development of biofortified lentil cultivars for global breeding programs to generate promising genotypes with low phytic acid and phytic acid/micronutrient ratio to combat micronutrient malnutrition.